Fabrizio De André, il tema dell’incontro nella dialettica testuale di Storia di un impiegato - Bellante, Emanuele (L’ospite ingrato, 2025)
This article proposes an analysis of the theme of encounter in the textual dialectic of Fabrizio De André’s concept album Storia di un impiegato (1973), focusing solely on the planes of inventio and dispositio, in other words content and structure, according to the chronotopic schemes proposed by contemporary literary criticism. The article highlights the narrative importance of the lyrics of Nella mia ora di libertà, since, as they close both the fabula and the plot of the whole concept album, they represent the last state of the last moment of the dialectic that Storia di un impiegato represents.